(untitled) (EDUCATION IN THE 21ST CENTURY, 2024)
To meet the academic and professional needs of the contemporary language learner, repositioning ESP for Diplomacy at the centre of the English programme at the Faculty of International Relations of YSU has been a significant adjustment, and to organize efficient educational process, along with developing proper educational materials, a deeper knowledge of the learner is an essential requirement. Based on a survey conducted among II, III and IV year students, the article discusses the students’ vision of the transfer from General English to ESP, the dynamics of the evolution of their ESP language awareness combined with the advance of their self-awareness and personal growth. The cognitive transition from General English to ESP requires certain time, when students gradually come to realize the specifics of the profession they have chosen. The rigorous curriculum, academic requirements, intensive educational programmes and profession-oriented student life, contribute to the dynamic development of personal growth and approaches. Having clear orientation of their goals, motivations, learning strategies and professional outlook, students demonstrate a firm resolve to acquire Diplomatic English in the university environment, claiming that Language Centres are best at teaching General English.